2003
DOI: 10.1111/j.1530-0277.2003.tb04404.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Prenatal Ethanol Exposure Alters Ionotropic Glutamate Receptor Subunit Protein Levels in the Adult Guinea Pig Cerebral Cortex

Abstract: These results demonstrate that chronic prenatal ethanol exposure produces long-lasting effects on the subunit composition of NMDA and AMPA receptors in the cerebral cortex of the adult guinea pig.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…These adaptations can lead to prolonged or permanent changes in the structure and function of neurons. There is growing evidence that CET causes alterations in NMDAR subunit levels and composition (Chen et al, 1999;Dettmer et al, 2003;Kalluri et al, 1998;Kumari and Ticku, 2000;Snell et al, 1996;Thomas et al, 1998;Trevisan et al, 1994;Winkler et al, 1999) that could lead to changes in synaptic transmission at glutamatergic synapses. We previously reported that prolonged ethanol caused an increased sensitivity of postsynaptic NMDARs and of presynaptic glutamate release to acute ethanol in CeA (Roberto et al, 2004b).…”
Section: Discussionmentioning
confidence: 99%
“…These adaptations can lead to prolonged or permanent changes in the structure and function of neurons. There is growing evidence that CET causes alterations in NMDAR subunit levels and composition (Chen et al, 1999;Dettmer et al, 2003;Kalluri et al, 1998;Kumari and Ticku, 2000;Snell et al, 1996;Thomas et al, 1998;Trevisan et al, 1994;Winkler et al, 1999) that could lead to changes in synaptic transmission at glutamatergic synapses. We previously reported that prolonged ethanol caused an increased sensitivity of postsynaptic NMDARs and of presynaptic glutamate release to acute ethanol in CeA (Roberto et al, 2004b).…”
Section: Discussionmentioning
confidence: 99%
“…1A, 820 ± 55, 388 ± 44, and 242 ± 32 % of control, respectively) without affecting cAMP levels in these cultures. EHNA accentuated the effect of NMDA on cGMP in DIV 8,13, and 21 cultures (Fig. 1A, 5651 ± 343, 2035 ± 154, and 1152 ± 140 % of control, respectively).…”
Section: Resultsmentioning
confidence: 86%
“…Effect of NMDA receptor activity and PDE activity on cAMP and cGMP levels in maturing primary cortical neuronal cultures Acutely treating primary cortical neuronal cultures with NMDA (30 μM; 15 min) increased cGMP in DIV 8,13, and 21 cultures (Fig. 1A, 744 ± 55, 332 ± 50, and 255 ± 32 % of control, respectively).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations